Chicken soup for the soul Christian kids : stories to inspire, amuse, and warm the hearts of Christian kids and their parents - Canfield, Jack 1944; Hansen, Mark Victor; Newmark, Amy (Chicken Soup for the Soul, 2008)
A collection of 101 of the best stories and poems from Chicken Soup's library, written by Christian parents and children about faith, family life, friends, pets, growing up, loss and leading a Christian life, based on faith, hope, and Christian values. Also contains children's prayers. All stories are appropriate for parents to share with children and stories are of interest to parents and children up to the early teen years.